A Comprehensive Review on Physical and Mechanical Properties of Polymer as Concrete Material - Mohd Yusof, Mohd Yusri; Shahidan, Shahiron (Recent Trends in Civil Engineering and Built Environment, 2024)
Polymers, the most malleable of all materials, have gained widespread acceptance and recognition due to their chemical, physical, and biological inertness as well as their lifespan, but if they are not recycled, they negatively harm the environment. The focus of this research is to conduct a comprehensive evaluation of the existing research on the use of polymers in concrete and to compare the physical and mechanical properties of polymer concrete to those of conventional cement concrete. The variable parameters such as resin / binder type used, the additives / microfillers used, and the properties evaluated from 20 previous study were listed, and the observations on its physical or mechanical properties were classified and reviewed. The elastic modulus and density of polymer concrete increase with polymer binder concentration (10-20%), water absorption is low, and porosity increases with resin-to-aggregate ratio as setting time reduces. Polymer concrete’s compressive, flexural, and tensile strengths increase with finer particles, adequate micro-filler content, and stronger binder. Future study suggests using other forms of polymer such as acrylic resin with different additives such as coal bottom ash (CBA) at varying ratios.